Ecolinguistic study of the writing works of achieving students Bali State Polytechnic in 2020 - Paulus Subiyanto; I Ketut Sadia; IGA Paramita Dewi (Politeknik Negeri Bali, 2020)
Bali State Polytechnic (PNB) has used the label